Arabidopsis CMT3 activity is positively regulated by AtSIZ1-mediated sumoylation. (October 2015) - Kim, Do Youn; Han, Yun Jung; Kim, Sung-Il; Song, Jong Tae; Seo, Hak Soo
Highlights: AtSIZ1 sumoylates DNA methyltransferase CMT3 through a direct interaction Sumoylation enhances the DNA methylation activity of CMT3 Genome methylation level is down-regulated in siz1-2 and cmt3 mutants than wild type Genome methylation level in siz1-2 mutants is lower compared to that in cmt3 mutants The methylation of CMT3 target genes is regulated by AtSIZ1-mediated sumoylation of CMT3 Abstract: The activities of mammalian DNA and histone methyltransferases are regulated by post-translational modifications such as phosphorylation and sumoylation; however, it is unclear how the activities of these enzymes are regulated at the post-translational level in plants. Here, we demonstrate that the DNA methylation activity of Arabidopsis CHROMOMETHYLASE 3 (CMT3) is positively regulated by the E3 SUMO ligase AtSIZ1. The methylation level of the Arabidopsis genome, including transposons, was significantly lower in the siz1-2 mutant than in wild-type plants. CMT3 was sumoylated by the E3 ligase activity of AtSIZ1 through a direct interaction, and the DNA methyltransferase activity of CMT3 was enhanced by this modification. In addition, the methylation levels of a large number of genes, including the nitrate reductase gene NIA2, were lower in siz1-2 and cmt3 plants than in wild-type plants. Furthermore, the CHG methylation activity of CMT3 was specific for NIA2 and not NIA1 (the other nitrate reductase gene in Arabidopsis ), indicating that CMT3 selectively regulates the CHG methylation levels of target genes. Taken together, our results indicate that the sumoylation of CMT3 is critical for its role in the control of gene expression and that AtSIZ1 positively controls the epigenetic repression of CMT3-mediated gene expression.